Efficacy and Safety of Artemisinin-Piperaquine for the Treatment of Uncomplicated Malaria: A Systematic Review - Wang, Qi; Zou, Yuanyuan; Pan, Ziyi; Zhang, Hongying; Deng, Changsheng; Yuan, Yueming; Guo, Jiawen; Tang, Yexiao; Julie, Nadia; Wu, Wanting; Li, Guoming; Li, Mingqiang; et al. (Frontiers in Pharmacology, 2020)
Objective: The World Health Organization recommends artemisinin-based combination therapies (ACTs) for the treatment of uncomplicated malaria to improve the therapeutic efficacy and limit the choice of drug-resistant parasites. This systematic review and meta-analysis aimed to evaluate the comparative efficacy and safety of artemisinin-piperaquine (AP) in the treatment of uncomplicated malaria relative to other commonly used ACTs. Methods: As per the PRISMA guidelines, the EMBASE, MEDLINE, the Google Scholar Library ，and Cochrane library databases were systematically searched from inception until July 2020 with the following terms: “artemisinin-piperaquine” or “AP”. Only randomized controlled trials (RCTs) were included. The competing interventions included dihydroartemisinin–piperaquine (DHA-PPQ), artemether–lumefentrine (AL,Coartem), artesunate-melfloquine(ASAM) and artesunate-amodiaquine (ASAQ, Artekin). Single-arm clinical trial on AP was also assessed. The reported outcomes, including the overall response, cure rate, fever and parasite clearance time, hematology, biochemistry, electrocardiogram (ECG), adverse events, recurrence rate, and sensitivity analyses, were systematically investigated. All data were analyzed using the Review Manager 5.3. Results: A total of 7 studies were reviewed, including 5 RCTs and 2 single-arm studies. A pooled analysis of 5 RCTs (n = 772) revealed a comparable efficacy on polymerase chain reaction (PCR)-confirmed cure rate between AP and competing interventions in treating uncomplicated malaria. As for the fever and parasite clearance time, due to the lack of complete data in some studies , only 3 studies’ data chould be used. The patients showed good tolerance to all drugs, and some side-effects (such as headache, anoxia, vomiting, nausea, and dizziness) were reported for every group, but they were self-limited and showed no significant difference. Conclusions: AP appeared to show similar efficacy and safety, with a simpler mode of administration and easier compliance when compared with other ACTs used in the treatment of uncomplicated malaria. Considering that the potential evolution of drug resistance is of a great concern, additional RCTs with high-quality and more rigorous design are warranted to substantiate the efficacy and safety in different populations and epidemiological regions.